From AMANDA to IceCube - Ribordy, M; Achterberg, A; Ackermann, M; Ahrens, J; Atlee, D W; Bahcall, J N; Bai, X; Baret, B; Bartelt, M; Bay, R; Barwick, S W; Beattie, K; et al. (2005)
The first string of the neoteric high energy neutrino telescope IceCube successfully began operating in January 2005. It is anticipated that upon completion the new detector will vastly increase the sensitivity and extend the reach of AMANDA to higher energies. A discussion of the IceCube's discovery potential for extra-terrestrial neutrinos, together with the prospects of new physics derived from the ongoing AMANDA research will be the focus of this paper. Preliminary results of the first antarctic high energy neutrino telescope AMANDA searching in the muon neutrino channel for localized and diffuse excess of extra-terrestrial neutrinos will be reviewed using data collected between 2000 and 2003. Neutrino flux limits obtained with the all-flavor dedicated UHE and cascade analyses will be described. A first neutrino spectrum above one TeV in agreement with atmospheric neutrino flux expectations and no extra-terrestrial contribution will be presented, followed by a discussion of a limit for neutralino CDM candidates annihilating in the center of the Sun.